Increased incidence of postmyocardial infarction ventricular septal defects during Covid‐19 pandemic: A case series. Issue 6 (21st March 2022) - D' Abramo, M.; Saltarocchi, S.; Vignaroli, W.; Chourda, E.; Vinciguerra, M.; Romiti, S.; Melina, G.; Greco, E.; Miraldi, F.
Abstract: Introduction: Ventricular septal defect (VSD) is one of the mechanical complications of acute myocardial infarction (MI), whose incidence has been decreasing throughout the years because of the emergence of different reperfusion therapy strategies. Methods: We present a series of seven patients who underwent surgery for post‐MI VSD repair in our institution in the period between March 2020 and June 2021. Discussion: During the recent SARS‐COV2 pandemic, time to hospital admission increased due to patients being overcautious out of fear of exposing themselves to COVID‐19. The increased time to hospital admission, with associated late reperfusion therapy and delayed PCI, is closely related to an augmented incidence of post‐myocardial infarction mechanical complications such as ventricular septal defects. For this reason, we witnessed an increase in the incidence of post‐MI VSD. Conclusion: Fear of exposure to SARS‐COV2 in the medical environment was a major source of concern for all our patients. The target of hospital policy should be to reassure patients of freedom from COVID in the emergency department and cardiac wards in order to prevent such dreadful complications.